Student-teachers' perspectives of the role of environmental education in geography education - Symmonds, Joanne (Rhodes University, Faculty of Education, Department of Education, 1997)
The ideas contained in socially critical Environmental Education cannot be ignored given the current environmental crisis and the need to achieve democracy in South African society. In order to achieve this learners need to develop the skills to make informed decisions which will facilitate the achievement of a sustainable society. It is the contention of this research that a socially critical Environmental Education approach to education can facilitate the above. Teachers of formal secondary school Geography Education are in the position to implement socially critical Environmental Education into their teaching. This study therefore investigates the perspectives of student teachers regarding the role of Environmental Education in secondary school Geography Education. This was done within the Interpretative Paradigm using a case study which involved five Higher Diploma in Education Geography method students. The research has revealed that even though the Geography method students have been exposed to an Environmental Education course, in their teaching preparation and are motivated to use it, they have limited understanding of the theory underpinning Environmental Education and how to apply it to their Geography teaching. The problems of bridging theory and practice was apparent. Recommendations are made as how to best facilitate the gap between theory and practice.
Keywords: Geography -- Study and teaching -- Environmental aspects; Environmental education